Hippocampal neurochemical markers in bipolar disorder patients following the first-manic episode: A prospective 12-month proton magnetic resonance spectroscopy study. (January 2017) - Silveira, Leonardo E; Bond, David J; MacMillan, Erin Leigh; Kozicky, Jan-Marie; Muralidharan, Kesavan; Bücker, Joana; Rosa, Adriane Ribeiro; Kapczinski, Flavio; Yatham, Lakshmi N
Objective: Previous studies reported decreased N -acetyl aspartate and increased Glx (the sum of glutamate plus glutamine) in bipolar disorder. Since these studies included patients at different stages of illness, it is unknown whether these changes have a causal role or a consequence of multiple episodes and treatments. The studies in early-stage bipolar disorder patients have the potential to provide answers to these issues. Therefore, we evaluated N -acetyl aspartate and Glx levels in hippocampi of first-episode bipolar disorder patients and health subjects at baseline and at 12 months, and examined the impact of episode recurrence on these measures. Method: We used single-voxel proton magnetic resonance spectroscopy to compare the hippocampal neurometabolites ( N -acetyl aspartate and Glx) levels between 41 patients with bipolar disorder following recovery from their first-manic episode and 27 matched healthy subjects at recruitment and 12 months later. We also compared N -acetyl aspartate and Glx levels between patients who had a recurrence of a mood episode and those who did not. Results: There was no main effect of either group (diagnosis) or time for hippocampal N -acetyl aspartate and Glx levels in bipolar disorder patients and healthy subjects. We also did not find any group-by-time interaction for the levels of these metabolites. There were also no differences in N -acetyl aspartate and Glx between patients who experienced a recurrence of a mood episode and those who did not over 12-month follow-up. Conclusion: Our data suggest that N -acetyl aspartate and Glx levels are not altered in early stage bipolar disorder. Further, these data suggest that episode recurrence in early stages does not have a significant impact on the levels of these metabolites. These may suggest that there may be an early window for intervention to potentially arrest neuroprogression of the disease.